Concentration of PM2,5 and Characteristic Analysis of Workers with Health Complaints Smoked Fish Workers in Tambak Wedi Village Surabaya - Dwi Sinta Nirmala; Corie Indria Prasasti (JURNAL KESEHATAN LINGKUNGAN, 2015)
Abstract: Smoked fish in Tambak  Wedi village Surabaya  using  coconut shell as the main fuel. Combustion of coconut shell in the process of smoked fish produced pollutants  PM2,5 that can cause health problems for workers.  The purpose of this study  was  to measure the consentration of PM2,5 and identify worker  characteristics that affect  worker  health complaints in the smoked fish Tambak  Wedi Village Surabaya.This study was observational descriptive study used cross sectional design. This study  was  conducted on  June,  2014  by using  questionnaire, interview,  and  observation with the sample was  26 respondents. The independent variables  were  PM2,5, age,  year of works, lenght  of employment, medical history, use  of PPE and work position. PM2,5 measurement using  a Haz-Dust EPAM 5000 for an hour and data collection characteristics of workers  using  a questionnaire and interview method. The results  of the study,  it found  that concentration of PM2,5 at 8 location  of Tambak  Wedi village smoked fish exceed  environmental requirements. Health complaints experienced by workers  in the  form of eye  complaints, highest perceived by workers  were  an eye  sore (100%),  while the  highest respiratory complaints perceived by workers  were  shortness of breath (80.8%).  Worker at smoked fish have chance to get respiratory problems and eye  irritation. The suggestion for workers  must  use  PPE, use chimney and check their health periodically  to health clinics  in Tambak  Wedi Surabaya.Keywords: Smoked  fish, PM2,5, health complaints